Saúde e espiritualidade. Contribuição dos presbíteros nos hospitais - Taitson, Paulo Franco (Revista eclesiástica brasileira, 2015)
This article investigates the potential contribution of the pastoral care provided in hospitals by hospital chaplains, as part of an integrated view of patient care, particularly in institutions dealing with severe disease. Improvements are needed on several fronts to professionalize the pastoral care provided in hospitals and modernize the figure of the chaplain. These improvements include better relations between modern chaplains and the hospital organization and scientific world; more focus on a scientific approach to their activities and on evaluating the efficacy of pastoral care activities; greater involvement in the multidisciplinary patient care teams, of which the hospital chaplains are an integral part.